Socialscapes and Abstractions: An Appraisal of Richard A. Horsley’s Theorizing of Antiquity - Rollens, Sarah E. (Journal for the study of the historical Jesus, 2020)
Richard A. Horsley’s work on Second Temple Judaism and early Christianity has been widely influential. In particular, his theorizing of the social world in which early Jews and Christians were embedded has significantly advanced biblical studies. This article engages with several of the most prominent analytical categories in his work (peasant, retainer, resistance, and renewal) with a view toward investigating their conceptual origins and probing their analytical utility.